2022
DOI: 10.6065/apem.2142186.093
|View full text |Cite
|
Sign up to set email alerts
|

The association between idiopathic scoliosis and growth hormone treatment in short children

Abstract: Purpose: Idiopathic scoliosis is the most common form of scoliosis, and the risk of onset and progression has been found to correlate with growth spurts. Therefore, treatment with recombinant human growth hormone (GH) treatment in short children may initiate and/or aggravate scoliosis. The aim of this study was to investigate the relationship between idiopathic scoliosis and GH treatment in short children.Methods: The medical records of 113 subjects seen at the participating institution between January 2010 an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…The association between GH and scoliosis remains unclear. [25][26][27][28][29][30][31] Further understanding of this issue may be achieved by demonstrating the characteristics of scoliosis among the 3 types of short stature that have different GH concentrations and exploring the role of rhGH on scoliosis. Our results showed that no differences were observed in the prevalence of scoliosis and the incidence of scoliosis development and progression among the three types of short stature.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The association between GH and scoliosis remains unclear. [25][26][27][28][29][30][31] Further understanding of this issue may be achieved by demonstrating the characteristics of scoliosis among the 3 types of short stature that have different GH concentrations and exploring the role of rhGH on scoliosis. Our results showed that no differences were observed in the prevalence of scoliosis and the incidence of scoliosis development and progression among the three types of short stature.…”
Section: Discussionmentioning
confidence: 99%
“…The association between GH and scoliosis remains unclear 25–31 . Further understanding of this issue may be achieved by demonstrating the characteristics of scoliosis among the 3 types of short stature that have different GH concentrations and exploring the role of rhGH on scoliosis.…”
Section: Discussionmentioning
confidence: 99%
“…Histomorphological studies showed that compared with unaffected individuals, bone volume fraction, trabecular bone thickness, and bone cell and osteoblast density were decreased in AIS patients. 7 In addition, studies have found that the risk of developing idiopathic scoliosis is significantly correlated with the duration of rapid linear bone growth, especially with the peak rate of spinal growth. [8][9][10][11] Secondly, the ability of bone growth and development is represented by bone maturity.…”
Section: Scoliosismentioning
confidence: 99%
“…The decrease in bone density caused by hormone‐related abnormalities may be one of the core contents of the pathogenesis of AIS. Histomorphological studies showed that compared with unaffected individuals, bone volume fraction, trabecular bone thickness, and bone cell and osteoblast density were decreased in AIS patients 7 . In addition, studies have found that the risk of developing idiopathic scoliosis is significantly correlated with the duration of rapid linear bone growth, especially with the peak rate of spinal growth 8–11 .…”
Section: Scoliosismentioning
confidence: 99%
“…One study suggested that about 4% of children with ISS who received rhGH therapy developed scoliosis, and this incidence was concordant with that of a general population without rhGH treatment [ 8 ]. A study by Park et al [ 9 ] also reported that rhGH therapy was not associated with development or aggravation of idiopathic scoliosis, with no significant differences in average Cobb angle (6.2° vs. 6.1°, P =0.842) or prevalence of scoliosis (9.7% vs. 13.3%, P =0.481) before and after one year of GH treatment in 113 subjects who were diagnosed with GHD, SGA, or ISS.…”
mentioning
confidence: 97%